Cerium-induced lattice disordering in Co-based nanocatalysts promoting the hydrazine electro-oxidation behavior. Issue 48 (26th May 2022) - Li, Jiechen; Dong, Changgang; Guo, Min; Gao, Wen; Kang, Luyao; Lei, Fengcai; Hao, Pin; Xie, Junfeng; Tang, Bo
Abstract : In this work, Ce incorporation in encapsulated Co-based nanocatalysts was achieved, leading to the formation of lattice-disordered oxide nanolayers with enriched active sites and optimized intrinsic activity for hydrazine electro-oxidation. Abstract : In this work, cerium-incorporated Co-based catalysts encapsulated in nitrogen-doped carbon were fabricated for the electrocatalytic hydrazine oxidation reaction (HzOR). The Ce incorporation could lead to the formation of surface oxide nanolayers with a disordered lattice, endowing the catalyst with enriched active sites and enhanced intrinsic activity for promoted HzOR.